Dostupné bydlení - Praha Vršovice - Doležalová, Kateřina; Kateřina Doležalová (České vysoké učení technické v Praze, 2023)
Bytový dům vznikl jako součást nového urbanismu na místě bývalého areálu továrny Koh-i-noor Waldes ve Vršovicích. Stavba je umístěna na ulici Vršovická a nově vzniklém náměstí, které je středem navrženého bloku. Cílem bylo vytvořit dostupné bydlení s výhodou komunitních prostorů, jako jsou například dvě velké střešní zahrady. Dům nabízí také komerční prostory a kavárnu s možností posezení ve vnitrobloku u zachovaného komína.

The apartment building is a part of a new urban planning project in place of the former site of the Koh-i-noor Waldes factory in Vršovice. The building is located on Vršovická Street and newly created square which is the center of the new block. The aim was to create affordable housing with the advantage of community spaces such as two large rooftop gardens. The house also offers commercial spaces and a café with the option of outdoor seating on the square by the chimney.
Affordable Housing - Prague Vršovice
Keywords: bytový dům; Koh-i-noor Waldes; Vršovice; dostupné bydlení; apartment building; Koh-i-noor Waldes; affordable housing; Vršovice